A genre analysis of online food and restaurant advertisements on Groupon / Anis Amirah Mohamad Fadillah - Anis Amirah, Mohamad Fadillah (2018)
Groupon is a deal-based website that offers discounted gift certificates which can be used at local or national companies. The deals offered cover a wide range of products and services from leisure, entertainment, food and beverages, health, beauty, travel to education. This is a genre analysis study of online food and restaurant advertisements which appear on the Groupon website. This study attempts to investigate how information is structured on the Groupon in terms of its rhetorical structure and linguistic features to attract potential customers to purchase the deal. The study also investigates the most common linguistic features found in the online food and restaurant advertisements in order to serve the informative and persuasive communicative purposes. The nine-move structure for advertisements introduced by Kathpalia (1992) and Bhatia (2004) is adopted as a framework for analysing the data in this study. Twenty Groupon deals of food and restaurant are collected. The moves found in each Groupon deal are identified and the frequency of occurrence of each move is recorded. Adapting Kathpalia’s (1992) and Bhatia’s (2004) framework, seven moves were identified as most obligatory from the data collected which are Headlines, Targeting the Market, Detailing the Product, Establishing Credentials, Offering Incentives, Using Pressure Tactics and Soliciting Response. All of these moves appear 100% for their frequency counts in the analysis of the data. In addition, two new moves are also established to be the most obligatory moves in this study; Locating the Product or Service Provider and Providing Related Information via Links whereas the Celebrity or Typical User Endorsement is the least. It is noted that the visuals also play a significant role in realising the moves specifically to help readers visualise what is being offered in the online food and restaurant advertisements in the most attractive manner. The most common linguistic features are identified in the samples in realising the moves in the online advertisements. They are the second person interpersonal pronoun ‘you’ and possessive adjective ‘your’, adjectives, binomial or multinomial expressions, repetitions, ellipsis and imperatives. It is hoped that this study would provide insights into the way the advertisers utilise their knowledge to accomplish their advertisements as well as to reach their intended audience, and to recommend a structure that may effectively attract potential consumers, which can also provide pedagogical implications for teachers of English Specific Purposes in a practical ESP class. The results of this study may facilitate the advertisers to produce a more effective online advertising. Thus, this would help the advertisers and the writers to decide what information should be used in publishing the successful online advertisements and creating an effective Groupon website.